THE USE OF ARTIFICIAL INTELLIGENCE METHODS IN TEACHING MODERN COMPUTER SCIENCE (Web of Technology: Multidimensional Research Journal, 2024)
Artificial Intelligence (AI) has transformed computer science education by enhancing teaching methodologies, personalizing learning, and streamlining assessment. This paper discusses AI techniques, such as machine learning (ML) and natural language processing (NLP), that optimize computer science instruction, thereby improving student engagement and comprehension